DETERMINE THE LEVEL OF USE MINERAL-VITAMIN COMPLEX IN THE DIETS ON THE WEIGHT OF THE SLAUGHTER AND CARCASS OF THE PIG BREED FROM THE AGE OF 6 MONTHS - I W.A.A, Nadi; Putri, T. I.; Utami, I. A. P. (Jurnal Peternakan Tropika; Vol 7 No 1 (2019): Vol. 7 Isssues 1 (2019); January - April 2019, 2019)
This study aims to determine the level of use mineral-vitamin complex in the diets on the weight of the slaughter and carcass of the pig breed from the age of 6 months. This research was conducted for 16 weeks in banjar lebah jadi, village jadi, Kediri, Tabanan. The design used was Randomized Block Design (RBD) consisting of 3 treatments and 4 replications/blocks, clustering based on weight. The treatments were attempted diets without of mineral-vitamin complex as the control (A), the diets with 0.10% mineral supplementation-vitamin complex (B), and 0.20% diets supplemented mineral-vitamin complex (C). The variables observed in this study were cutting weight, carcass weight, carcass percentage and back fat thickness. The result showed that the use mineral-vitamin complex at the level of 0,10 % and 0,20 % was not significantly different (P>0,05) in the cutting weight and carcass weight, in the percentage of carcasses there was an increase in treatment A and statistically significantly different (P<0,05). The use of mineral-vitamin complex 0,10 % and 0,20 % there was a decrease in back fat thickness of 17,0 % and 21,0 % of treatment A and was statistically significantly different (P<0,05). Based on the results of the above research, it can be concluded that diets using mineral-vitamin complex as much as 0,20 % in crossbred pigs can increase the percentage of carcess and reduce the back fat thickness   Keyword s : cutting weight, carcass, cross breed pigs, mineral-vitamin complex